ABRELATAS AND SCARECROW NOUNS: EXOCENTRIC VERB-NOUN COMPOUNDS. AS ILLUSTRATIONS OF BASIC PRINCIPLES OF COGNITIVE GRAMMAR - Tuggy, David (International Journal of English Studies, 2003)
Spanish and English have exocentric verb+obiect = subiect/instrument compounds, such as abrelatas (opens-cans) ’can-opener’ and scarecrow. They share a general constructional pattem, consist of "clumps" or subfamilies of forms, and have a negative or jocular tendency. They differ in their individual compounds, subfamilies and constructional prototypes. The Spanish construction is a widely productive, major mechanism for naming instruments; the English construction names subjects, and is a minor pattem currently productive only in one subfamily. Exceptional forms in both languages approach each other’s prototype. In both languages the category fits into wider families or categories of constructions, but those wider families are different. These patterns illuminate basic tenets of Cognitive grammar, including: (1) usage-based grammar. (2) Multiple pattems. (3) Lower-leve1 outranking higher-leve1 pattems. (4) Functional motivation, but ( 5 ) persistence of pattems despite absence of functionality. These considerations underline (6) the insufficiency of models positing innate, absolute, few and simple rules.